Basin-scale tracer replacement timescales in a one-degree global OGCM - Kusahara, Kazuya; Tatebe, Hiroaki (Frontiers in Marine Science, 2023)
This study investigates basin-scale tracer replacement timescales of the two polar oceans and the Atlantic, Indian, and Pacific Oceans using a one-degree global ocean-sea ice model that represents oceans under the largest Antarctic ice shelves, the Filchner-Ronne and Ross Ice Shelf (FRIS and RIS). After a long spin-up with present-day surface boundary conditions, we confirm that the model has a typical representation of wind-driven and thermohaline circulations in one-degree ocean models. We use virtual passive tracers placed in the five oceans and examine the behavior of the passive tracers to estimate the tracer replacement timescales and pathways of the basin-scale ocean waters. Replacement timescales in the polar oceans (114 years for the Southern Ocean and 109 years for the Arctic Ocean) are found to be shorter than those in the three oceans (217 years for the Atlantic Ocean, 163 years for the Indian Ocean, and 338 years for the Pacific Ocean). The Southern Ocean tracer has two clear pathways to the Northern Hemisphere: the surface route in the Atlantic Ocean and the bottom route in the Pacific and Indian Oceans. This surface route is a rapid conduit to transport the Southern Ocean signal to the North Atlantic and Arctic Oceans. The Atlantic Ocean tracer is transported to both polar regions along the North Atlantic Current and the Antarctic Circumpolar Current (ACC). The tracer experiments clearly demonstrate that Atlantic Meridional Overturning Circulation (AMOC) plays a vital role in transporting the water masses in the Atlantic and Arctic Oceans to the Southern Ocean. The southward flow of the AMOC at the intermediate depths carries the northern waters to the ACC region, and then the water spreads over the Southern Ocean along the eastward-flowing ACC. The decay timescales of water in the ice-shelf cavities exposed to the water outside the Southern Ocean are estimated to be approximately 150 years for both the FIRS and RIS. The decay timescales in the Antarctic coastal region are short at the surface and long in the deep layers, with a noticeable reduction in the areas where ACC flows southward toward the Antarctic continent.